A new genus and two new species of Neotropical Myodochini (Hemiptera: Heteroptera: Rhyparochromidae) - Dellapé, Pablo Matías (2012)
A new genus and 2 new species of Neotropical myodochines are described from Trinidad and Tobago, and Peru. Each species is diagnosed and described, and adult photographs and illustrations of the male genitalia are provided to facilitate identification. The studied specimens are deposited in the American Museum of Natural History (AMNH, New York, USA), and Museo de La Plata (MLP, La Plata, Argentina).